ROLE OF THE KERALA STATE COOPERATIVE CONSUMERS FEDERATION IN THE RETAIL MARKETS – AN OVER VIEW - Sameera P. (Abhinav International Monthly Refereed Journal of Research In Management & Technology, 2014)
The kerala model of development is famous for the achievements it has contributed for the development of social infrastructure like health care and education. For the last several years, things are changing all over the world in a dramatic manner and in many cases these changes are going beyond our expectation and recognition. Both organized and unorganized retail chains are mushrooming all over the Kerala. The consumer dynamics of Kerala are changing and the retailers have to keep in track of this for formulating suitable strategies and policies. Retailing is considered as the largest sector both in contribution to GDP and employment among many countries in the world. It plays a predominant position in the economies of all developed countries. The Kerala State Co- operative Consumers Federation Ltd is the most prominent among the cooperatives in India as it has more than 1232 consumer retail outlets in the state to supply consumer goods and to interfere and control the essential goods market. Here an attempt is done to describe the role and functions performed by the federation through its divisions and to get an overall understanding about the federation.